Post-cholecystectomy functional disorders of the sphincter of Oddi after - Yu. M. Pantsyrev; S. G. Shapoval’yants; S. A. Chernyakevich; A. G. Pankov; I. V. Babkova; S. Yu. Orlov; N. V. Zubova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study the results of complex investigation of patients with postcholecystectomy syndrome for the sake of diagnostics of functional disorders of the sphincter of Oddi (SO) and targeted treatment.Material and methods. Overall 70 patients mainly with biliary colic after cholecystectomy were included in original study. The complex investigation, that included laboratory methods, ultrasound investigation, including that with test meal, endosonography, endoscopic cholangiopancreatography excluded organic changes of pancreatobiliary system. Successful SO manometry was executed in 27 of 32 patients.Results. Functional SO disorders (spasm of papilla of Vater, hyper- and hypokinetic dyskinesia, increased frequency of contractions, local stenosis of papilla of Vater in combination to sphincter dysfunction) were diagnosed in all patients, who underwent endoscopic SO manometry. Treatment was prescription was differential, spasmolytic and prokinetic drugs were applied.